Beta‐Blockers increase the risk of being born small for gestational age or of being institutionalised during infancy. (17th March 2014) - Xie, R‐h; Guo, Y; Krewski, D; Mattison, D; Walker, MC; Nerenberg, K; Wen, SW
<x xml:space="preserve">Abstract</x> Objective To compare infant outcomes between mothers with hypertension treated by beta‐blockers alone and by methyldopa alone during pregnancy. Design Historical cohort study. Setting Saskatchewan, Canada. Population Women who delivered a singleton birth in Saskatchewan during the periods from 1 January 1980 to 30 June 1987 or from 1 January 1990 to 31 December 2005 (women who delivered between 1 July 1987 and 31 December 1989 were excluded because the information recorded on maternal drug use during pregnancy is incomplete) with a diagnosis of a hypertensive disorder during pregnancy, and who were dispensed only beta‐blockers (n = 416) or only methyldopa (n = 1000). Methods Occurrences of adverse infant outcomes were compared between women who received beta‐blockers only and women who received methyldopa only during pregnancy, first in all eligible women, and then in women with chronic hypertension and in women with gestational hypertension or pre‐eclampsia/eclampsia, separately. Multiple logistic regression analyses were performed to adjust for potential confounding. Main outcome measures Small for gestational age (SGA) < 10th percentile, SGA < 3rd percentile, preterm birth, stillbirth, institutionalisation for respiratory distress syndrome (RDS), sepsis, seizure during infancy, and infant death. Results Adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs) for infants born to mothers with chronic hypertension who were dispensed beta‐blockers only, as compared with infants born to mothers who were dispensed methyldopa only, during pregnancy were: 1.95 (1.21–3.15), 2.17 (1.06–4.44), and 2.17 (1.09–4.34), respectively, for SGA < 10th percentile, SGA < 3rd percentile, and being institutionalised during infancy. Conclusions For infants born to mothers with chronic hypertension, compared with those treated by methyldopa alone, those treated by beta‐blockers appear to be at increased rates of SGA and hospitalisation during infancy.